Differential cellular effects of old and new oral anticoagulants: consequences to the genesis and progression of atherosclerosis - Schurgers, Leon J.; Spronk, Henri M. H. (Thrombosis and Haemostasis, 2014)
The main purpose of anticoagulants is to diminish fibrin formation, thereby decreasing the risk of venous or arterial thrombosis. Vitamin K antagonist have been used for many decades in order to achieve reduced thrombotic risk, despite major drawbacks of this class of drugs such as cumbersome dossing and monitoring of anticoagulant status. To overcome these drawbacks of VKA, new classes of anticoagulants have been developed including oral anticoagulants for direct inhibition of either thrombin or factor Xa, which can be administrated in a fixed dose without monitoring. Coagulation factors can activate cellular protease-activated receptors, thereby inducing cellular processes as inflammation, apoptosis, migration, and fibrosis. Therefore, inhibition of coagulation proteases not only attenuates fibrin formation, but may also influence pathophysiological processes like vascular calcification and atherosclerosis. Animal models revealed that VKA therapy induced both intima and media calcification and accelerated plaque vulnerability, whereas specific and direct inhibition of thrombin or factor Xa attenuated atherosclerosis. In this review we provide an overview of old and new oral anticoagulants, as well discuss potential pleiotropic effects with regard to calcification and atherosclerosis. Although translation from animal model to clinical patients seems difficult at first sight, effort should be made to fully understand the clinical implications of long-term oral anticoagulant therapy on vascular side effects.
Keywords: Arterial thrombosis; arteriogenesis; atherothrombosis; vitamin K-dependent factors; atherosclerosis